Oculomotor Nerve Palsy due to an Odontogenic Abscess Originating from the Mandibular Third Molar - Hee-Keun Park; Moon-Key Kim; Sang-Hoon Kang (Hindawi Limited, 2012)
We report a case of oculomotor nerve palsy (ONP) as a result of odontogenic infection originating from the third molar, which is considered rare.